FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KESEGARAN JASMANI LANSIA LAKI-LAKI TIDAK ANEMIA - Yuniar Rosmalina; Dewi Permaesih; Fitrah Emawati; Reviana Christiani; Dangsia Moeloek; Susilowati Herman (Persagi, 2003)
FACTORS RELATED TO PHYSICAL FITNESS OF NON-ANEMIC MALE ELDERLYBackground: Physical fitness can be used as indicator of the community health including elderly people. One of the benefit is elderly could live independently and do their daily activities without assistant. Since there were some factors related to physical fitness of the elderly people. This study aim to determine what factors were associated with physical fitness of non anemic male elderly in rural and urban area. Methods: 217 non anemic male elderly in rural area and 289 in urban area were participated in this study. After screening on blood hemoglobin level an agreed to participate the measurement followed by physical fitness measurements. Nutritional status was calculated from their body weight and height. Structured questionnaire was used to obtain information on sociodemographic factors, sosial activities, daily physical activities. Semi-FFQ was applied to assess their energy and protein intake. Results: The proportion of elderly who had low level physical fitness was 57.1% in rural area and 82.6% in urban area. Statistical analysis shows that the level of physical fitness in rural area was significantly associated with sociodemographic characteristic (age, current occupational and economic burden), sosial activities (religious activities), life style (current and previous smoking status), health status (systolic and diastolic blood level), energy and protein intakes. In Urban area shows that the level of physical fitness was significantly associated with life style (current smoking status, physical activities level, nutrtitional status, health status (systolic blood level) and energy and protein intakes. Conclusions: Several factors which cause the difference of level physical fitness between elderly at rural and urban area were job status, economic burden, physical activity, and diastolic blood pressure.Keyword: physical fitness, elderly.